RACIAL STEREOTYPING OF HOMO SAPIENS AFRICANUS: A REVIEW OF ITS MYTH AND IMPACT ON DEVELOPMENTAL CAPACITY - Oppong, Seth (Africanus: Journal of Development Studies, 2016)
<span style="color: #000000; font-family: 'Arial Narrow', Arial, Helvetica, Tahoma, Geneva, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Generally, negative stereotypes have been shown to have negative impact on the performance of members of the social group that is the target of the stereotype. It is against the background of this evidence that this article argues that the negative stereotypes of perceived lower intelligence held against Africans has a similar impact on the general development of the continent. This article seeks to challenge this stereotype by tracing the source of this negative stereotype to David Hume and Immanuel Kant and by showing the initial errors they committed, which have influenced social science knowledge about race relations. Hume and Kant argue that Africans are naturally inferior to Whites, or are less intelligent and support their thesis with their contrived evidence that there has never been any civilised nations other than those developed by White people or any African scholars of eminence. Drawing on Anton Wilhelm Amo's negligence-ignorance thesis, this article proves that the Hume-Kantian argument and its supporting evidence are fallacious.